2008
DOI: 10.1016/j.chom.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The IL-8 Protease SpyCEP/ScpC of Group A Streptococcus Promotes Resistance to Neutrophil Killing

Abstract: SUMMARY Interleukin-8 (IL-8) promotes neutrophil-mediated host defense through its chemoattractant and immunostimulatory activities. The Group A Streptococcus (GAS) protease SpyCEP (also called ScpC) cleaves IL-8, and SpyCEP expression is strongly upregulated in vivo in the M1T1 GAS strains associated with life-threatening systemic disease including necrotizing fasciitis. Coupling allelic replacement with heterologous gene expression, we show that SpyCEP is necessary and sufficient for IL-8 degradation. SpyCEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(198 citation statements)
references
References 47 publications
(63 reference statements)
6
190
0
Order By: Relevance
“…Research over the past decade has now shown that three comparable mechanisms are also employed by pathogenic bacteria, viruses, and parasites: inhibition of NETs release, degradation of NETs, and resistance to NETs killing (Figure 2). Perhaps the best example of this is GAS, which has evolved mechanisms to evade NETs using all three of these strategies (10,(14)(15)(16)(17).…”
Section: Pathogen Evasion Of Netsmentioning
confidence: 99%
“…Research over the past decade has now shown that three comparable mechanisms are also employed by pathogenic bacteria, viruses, and parasites: inhibition of NETs release, degradation of NETs, and resistance to NETs killing (Figure 2). Perhaps the best example of this is GAS, which has evolved mechanisms to evade NETs using all three of these strategies (10,(14)(15)(16)(17).…”
Section: Pathogen Evasion Of Netsmentioning
confidence: 99%
“…The presence and kinetics of free circulating neutrophilderived DNA/NETs appear to serve as a useful marker of sepsis disease severity and multiple organ failure in patients following multiple traumas [84]. Specific bacterial products, such as the surface expressed M protein of S. pyogenes, or host chemokines, such as IL-8, can induce the production of NETs [85,86]. It is now recognized that certain leading leading bacterial pathogens, including Streptococcus pneumoniae and S. pyogenes, express broadspectrum DNAses that have recently been shown to dissolve NETs, allowing pathogen to escape entrapment and spread to produce systemic infection in the host into the host [87][88][89].…”
Section: Induction Of Neutrophil Extracellular Trap-associated Cell Dmentioning
confidence: 99%
“…While several studies have been conducted on S. iniae, attention to date has mainly focused on the so-called virulence factors SiM protein [2,5]. interleukin-8 protease [6], streptolysin S [7]. C5a peptidase [8], capsule [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%